Making a Difference in Educational Outcomes for Remote First Nations Students - Guenther, John; Lowe, Kevin; Burgess, Cathie; Vass, Greg; Moodie, Nikki (Springer International Publishing, 2023)
Education for Aboriginal and Torres Strait Islander (First Nations) students living in remote communities has long been seen as an intractable problem. Ten years of concerted effort under Closing the Gap and related policy initiatives has done little to improve outcomes beyond small, incremental improvements. Programs and strategies promising much have come and gone, and most have quietly gone by the wayside. This apparent failure leaves the context of remote education ripe for the picking. If we can demonstrate what works and why, it may provide an answer to the problem. This systematic review aims to uncover what research in the ten years from 2010 to 2020 reveals about what does and does not make a difference to outcomes for students. The review identified 36 papers that provide strong evidence to show what is and is not effective. The review also found several issues that have little or no evidence and which could be the subject of more research. No Full Text